Answer: Ck.12.org
Step-by-step explanation: Just read the book
Step-by-step explanation:
Sin: 2 square root 3: 4
Cos: 2:4
Tan: 2 square root 3: 2
Answer:
Step-by-step explanation:
Favorable outcome. To possible outcome
Answer:
![\displaystyle (7x - 8y) + (-6x - 6y) = x - 14y](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%287x%20-%208y%29%20%2B%20%28-6x%20-%206y%29%20%3D%20x%20-%2014y)
General Formulas and Concepts:
<u>Pre-Algebra</u>
Order of Operations: BPEMDAS
- Brackets
- Parenthesis
- Exponents
- Multiplication
- Division
- Addition
- Subtraction
<u>Algebra I</u>
Step-by-step explanation:
<u>Step 1: Define</u>
<em>Identify</em>
<em />
<em />
<em />
<u>Step 2: Simplify</u>
- Combine like terms (x):
![\displaystyle (7x - 8y) + (-6x - 6y) = x - 8y - 6y](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%287x%20-%208y%29%20%2B%20%28-6x%20-%206y%29%20%3D%20x%20-%208y%20-%206y)
- Combine like terms (y):
![\displaystyle (7x - 8y) + (-6x - 6y) = x - 14y](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%287x%20-%208y%29%20%2B%20%28-6x%20-%206y%29%20%3D%20x%20-%2014y)
Answer:
5n^2 - 3n - 8
Step-by-step explanation:
4n.5n - 4n.8 + 4.5n - 4.8
= 20n^2 - 32n + 20n - 32
= 20n^2 - 12n - 32
= 4 ( 5n^2 - 3n - 8 )
= 5n^2 - 3n - 8 [ answer ]